2011
DOI: 10.1093/cercor/bhr177
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Imitation: Toward a Neural Basis of Social Interaction

Abstract: Social interaction is a coregulated coupling activity that involves at least 2 autonomous agents. Numerous methodological and technical challenges impede the production of natural social interaction within an Magnetic Resonance Imaging environment under controlled conditions. To overcome the obstacle, we chose a simple format of social interaction, namely "interactive imitation" through a double-video system. We registered blood oxygen level-dependent activity of 23 participants during 2 imitative conditions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 57 publications
3
55
0
4
Order By: Relevance
“…The design of that study consisted of an innovative functional MRI set-up that enabled behavioural and brain recordings to be synchronized during online imitative interaction. We replicated previous findings demonstrating the existence of an imitative neural network (Iacoboni et al, 1999), and most importantly revealed the involvement of the dorsolateral prefrontal cortex and other regions in social anticipation and adjustment when free reciprocal imitation is in play (Guionnet et al, 2012). Further, we showed that imitating and being imitated activate similar brain areas.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The design of that study consisted of an innovative functional MRI set-up that enabled behavioural and brain recordings to be synchronized during online imitative interaction. We replicated previous findings demonstrating the existence of an imitative neural network (Iacoboni et al, 1999), and most importantly revealed the involvement of the dorsolateral prefrontal cortex and other regions in social anticipation and adjustment when free reciprocal imitation is in play (Guionnet et al, 2012). Further, we showed that imitating and being imitated activate similar brain areas.…”
supporting
confidence: 90%
“…Our procedure was inspired by our previous study conducted with typical adults (Guionnet et al, 2012). The design of that study consisted of an innovative functional MRI set-up that enabled behavioural and brain recordings to be synchronized during online imitative interaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…leaders) of action in reciprocal imitation paradigms in both interactive (Dumas et al, 2012, Guionnet et al, 2012) and non-interactive scenarios (Decety et al, 2002). These studies have shown activation of the inferior parietal cortex during initiation and imitation of stimuli, in the absence of interaction (Decety et al, 2002), as well as recruitment of fronto-parietal regions during interactive imitation (Guionnet et al, 2012). In contrast to these studies, the aim of the current study was to develop a two-brain analysis, which uses data from both brains to uncover the complementary neural mechanisms of spontaneous leaderfollower dyads in a tightly-coupled coordinative task.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the key estimate of the probability of leading generated from our combined PT and optimal categorization model correlated with activity in the Anterior Insula (aIns), a well-established integration hub proposed to combine internal and external states, together with estimated option values, to inform choice (60,61,(115)(116)(117)(118)(119).…”
Section: Model Fit Valuementioning
confidence: 99%